Reducing the Risk of Preterm Preeclampsia: Comparison of Two First Trimester Screening and Treatment Strategies in a Single Centre in Switzerland - Amylidi-Mohr, Sofia; Kubias, Jakub; Neumann, Stefanie; Surbek, Daniel; Risch, Lorenz; Raio, Luigi; Mosimann, Beatrice (Geburtshilfe und Frauenheilkunde, 2021)
Introduction First trimester screening for preeclampsia (PE) is based on the combined risks model. Recent trials demonstrate that variations in multiple of the medians (MoMs) of the screening markers influence the performance of the algorithm in different populations. The aim of this study is to compare the performance of the algorithm in two cohorts with different prevention strategies.Material and Methods All first trimester screening tests performed between January 2014 and April 2020 were included. Up to June 2017 pregnancies with a risk > 1 : 200 for early-onset PE (eoPE) were considered at risk and received 100 mg of aspirin (strategy A). From July 2017 onwards, pregnancies with a risk > 1 : 100 for preterm PE (pPE) received 150 mg of aspirin (strategy B). We compared the screen positive rates (SPR) and incidence of PE between the two screening approaches. Statistical analysis were performed with Graphpad 8.0.Results 3552 pregnancies were included; 1577 pregnancies were screened according to strategy A, 1975 pregnancies according to strategy B. The screen positive rate (SPR) for strategy A and B was 8.9 and 16.9% respectively (p < 0.0001) while the incidence of PE was 1.41 and 1.84% respectively (p = ns).Conclusion With a SPR of less than 10% we achieved a remarkably low rate of PE in our population, no further reduction in PE could be achieved by an increase in the SPR and LDA-prescription during the second screening period. The cut-off to define a pregnancy at risk for PE should be tailored to keep the SPR below 10% to avoid unnecessary treatment with aspirin.
Keywords: preeclampsia; first trimester screening; implementation